The Spanish King Alfonso XIII’s Humanitarian Work during World War I: The Creation of the European War Office (1914 – 1919) - Campa, Álison Gil (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
After 100 years, archival evidence and intellectual contributions have reached the public domain, permitting vibrant discourse on the First World War. Many commemorations focus on the particular national sacrifice rendered, but the war’s international character should also be remembered. While historians have analysed the belligerent nations, neutral countries like Spain have received little attention. Some European governments declared neutrality in 1914; several later joined the war. However, Spain stayed neutral throughout the conflict and also accomplished the unexpected. King Alfonso’s European War Office at Madrid’s Royal Palace combined personal and official humanitarian action, allowing Spain to pursue active neutrality in the First World War. The Office was formed in 1915 in response to Alfonso XIII’s high number of anxious demands regarding the location, care, and re-patriation of loved ones (both soldiers and civilians). It was handled by a small team of up to 50 staff members, assisted by Spain’s substantial diplomatic network overseas. The European War Office chose to file and maintain all missives from requestors, resulting in a significant collection of letters and files in the Royal Palace Archives. This article describes the humanitarian initiative created by the Spanish monarch, Alfonso XIII, during World War I. It was known as the Office of Pro Captives or Office of the Great European War. Because Spain stayed neutral during the conflict and because the king and the Spanish ambassadors in the countries that were fighting worked as peacemakers, thousands of people were able to find their missing loved ones.